Posttreatment of a brewery wastewater using a sequencing batch reactor - Ana C. Rodrigues (2001)
This study concerns the application of a sequencing batch reactor (SBR) for the posttreatment of an effluent rejected by an upflow anaerobic sludge blanket (UASB) reactor operating in a brewery. The goal was to achieve the required wastewater quality for discharge to surface water. The primary target was the removal of nitrogen compounds, but chemical oxygen demand and suspended solids were also concerns. Phosphorus concentration and protozoan population were also monitored during SBR operation. Two different strategies were tested: an operation based on an aerobic-anoxic sequence and another based on applying a predenitrification step, that is, an anoxic-aerobic-anoxic sequence. Ammonium (NH4-N) removal was achieved in all assays. Nitrification efficiency reached 97%, and the maximum observed rate was 0.175 kg NH4-N/kg volatile suspended solids.d. A denitrification process was detected during the aerated periods, despite a dissolved oxygen concentration in the bulk liquid of 2.8 to 3.7 mg O-2/L. However, denitrification was suppressed when the bulk liquid oxygen concentration was increased to 7 mg O-2/L. The carbon-to-nitrogen ratio of the UASB effluent was too low and hindered the postdenitrification phase. This fact was confirmed by complete nitrate removal when an acetate supplement was added. On the other hand, the insertion of a primary anoxic phase in the reaction cycle was the best treatment strategy, leading to nitrogen values within the legal framework. The protozoan population showed significant changes in response to the aerobic-anoxic conditions. However, periodic nonaerated conditions were not detrimental to aerobic protozoa, which recovered as soon as oxygen was again available.